Design and composition of synthetic fungal-bacterial microbial consortia that improve lignocellulolytic enzyme activity. (March 2017) - Hu, Jiajun; Xue, Yiyun; Guo, Hongcheng; Gao, Min-tian; Li, Jixiang; Zhang, Shiping; Tsang, Yiu Fai
Graphical abstract: Highlights: Synergistic microbial consortia were devised to produce lignocellulolytic enzymes. It was difficult to find two strains with positive synergistic interactions. Addition of a cellulolytic microbial community enriched the number of species. Positive response between strains could be studied using high-throughput sequence. Both bacterial and fungal strains play important roles in the interactions. Abstract: Microbial interactions are important for metabolism as they can improve or reduce metabolic efficiency. To improve lignocellulolytic enzyme activity, a series of synergistic microbial consortia of increasing diversity and complexity were devised using fungal strains, including Trichoderma reesei, Penicillium decumbens, Aspergillus tubingensis, and Aspergillus niger . However, when a screened microbial community with cellulolytic capacity was added to the consortia to increase the number of strains, it engendered more microbial interactions with the above strains and universally improved the β -glucosidase activity of the consortia. Analysis of the microbial community structure revealed that the bacteria in the consortia are more important for lignocellulolytic enzyme activity than the fungi. One fungal and 16 bacterial genera in the consortia may interact with T. reesei and are potential members of a devised synergistic microbial consortium. Such devised microbial consortia may potentially be applied to effectively and economically degrade lignocellulose.